Overview of Toddler Height and Weight in Patients with Malnutrition at the Dukuh Kupang Health Center, Surabaya - Binti Sholihah, Nindy Kurniati; Akas Yekti Pulih Asih (HM Publisher, 2023)
Children do not get enough energy intake, so the body will use energy reserves in the form of fat and protein to maintain important body functions. This can cause weight loss in children, especially if the nutritional deficiency lasts for a long time. Overall, a child's height and weight are very important in assessing a child's nutritional status because both are good indicators of growth and development. If there are disturbances in the growth and development of children, then this can be a sign that the child has nutritional problems that need to be taken seriously. This study aimed to determine the relationship between height and weight with malnutrition in infants at the Dukuh Kupang Health Center area as a descriptive observational study. The data used in this study were height and weight data as well as the nutritional status of infants obtained from Health Centers in the Dukuh Kupang Health Center area. Regression analysis was performed to determine whether height and weight have a significant effect on the nutritional status of infants. The results showed that height and weight had a significant effect on the nutritional status of infants, with significant regression coefficient values for each variable. In addition, the ANOVA test also shows that the regression model used is significant. These results can be used as a basis for improving public health programs related to the problem of malnutrition in toddlers in the Dukuh Kupang Health Center area.